Anti-inflammatory and anti-platelet activities of Avena Sativa are mediated through the inhibition of cyclooxygenase and lipoxygenase enzymes - Ahmed , Sagheer; Gul , Saima; Gul , Humera; Bangash , Muhammad Hanif (International Journal of Endorsing Health Science Research, 2013)
Avena sativa (AS) is a well-known food crop and an important medicinal plant. It has been used for the treatment of various diseases, particularly for the treatment of inflammatory and cardiovascular diseases. However, the scientific rationale and mechanisms by which it functions in these diseases is still un- known. This study was designed to explore the inhibitory activity of AS aqueous, n-hexane and butanolic fractions on arachidonic acid (AA) metabolism. For this purpose these fractions of AS were screened for the presence of activities against AA metabolites and their effectiveness was further evaluated by studying platelet aggregation induced by AA, adenosine diphosphate (ADP), platelet activating factor (PAF), and collageAA metabolism was studied by thin layer chromatography system while platelet aggregation was measured by dual channel Lumiaggregometer. Aqueous and n-hexane fractions of AS were totally ineffective against AA metabolism and platelet aggregation. However, butanolic fraction inhibited the AA metabolites- thromboxane B2 (TXB2) through cyclooxygenase (COX) pathway and lipoxygenase product-1 (LP-1) and 12-hydroxyeicosatetraenoic acids (12-HETE) through lipoxygenase (LOX) pathway. Similarly butanolic fraction of AS showed strong inhibition against AA, PAF-induced aggregation but was less potent against ADP.AS possesses components which can inhibit AA metabolism and platelet aggregation. This may be one of the underlying mechanisms of their actions in cardiovascular and inflammatory diseases.